OS8.5 How to assess meningioma therapy activity: The CEVOREM independent central review experience. (6th September 2019) - GRAILLON, T; Colin, T; Peyrière, H; Peyre, M; Tabouret, E; Campello, C; Idbaih, A; Boucekine, M; Figarella-Branger, D; Kalamarides, M; Dufour, H; Sanson, M; et al.
Abstract: BACKGROUND: Meningioma therapy efficiency is used to being assessed by 6 months progression survival rate (PFS6), which remains the most consensual criterion. Nevertheless, different patterns of meningiomas intrinsic aggressiveness and growth rates directly impact the PFS6 leading to unreliability of drug effect assessment. Moreover, therapeutic response remains rare in meningiomas. These points lead to consider classical and updated RANO criteria as not fully adapted to meningiomas. Based on phase II CEVOREM trial experience, we aim to improve the assessment of drugs efficiency in meningiomas via the determination of growth rate before and under treatment. MATERIAL AND METHODS: Twenty patients were included in Cevorem trial which tested the combination of octreotide and everolimus as previously described. MRI assessment was performed in the 3 to 6 preinclusion months, at inclusion then every 3 months. Progression was assessed by investigators according to RANO criteria. An independent central review was performed with 2 reviewers and 1 adjudicator: largest diameter, 2D maximal area as 3D volume were assessed by autosegmentation software (Brainlab). Results from central review were correlated to investigators assessment. 3D volume growth rate (3DVGR) was calculated using 2 different processes (one simple and one complex). Comparison of 3DVGR before vs. under treatment was performed. Meningioma growth under treatment was compared to theoretical meningioma growth based on preinclusion data using a model of meningioma growth. RESULTS: PFS6 assessed via the independent central review was in accordance with PFS6 assessed by investigators following RANO criteria. Then, we analyzed 3DVGR before and during therapy. Standard deviation was higher using the complex 3DVGR calculation process. A decrease of more than 50% of the 3DVGR was observed in 30/36 tumors at 3 months with the both calculation modes and could be considered as a threshold of drugs activity. Median volume growth rate decreased from 88.3 or 17.2%/3 months before inclusion to -2.2 or à -0.6 %/3mo at 3 months depending of the calculation mode (p <0.0002). Nevertheless, in our study, decrease in 3DVGR was associated with a prolonged free progression period when 3DVGR decreased around 0 or negative. Comparison of theoretical meningioma growth curve based on preinclusion data with under treatment growth curve is ongoing. Some limits remain: 3DVGR calculation remains directly related to the volume assessment accuracy and 3DVGR can be very high particularly in case of very small initial tumor which cannot be mitigated by current mathematical models. CONCLUSION: 3DVGR measurement during versus before seems as a sensitive and reliable tool which provides valuable comparison in a phase 2 study to assess drugs activity in meningioma in complement to PFS6. 3DVGR assessment should be considered in future clinical trials.